Android-Based E-Inventory System (Case Study: DPRD Kabupaten Berau) - Muhammad Daffa Firmansyah; Wahyu Sri Utami (Publikasi Indonesia, 2024)
Technology is a rapidly evolving field in recent times, capable of solving various problems across different sectors. One problem addressed in the government sector is the emergence of e-government, a movement where technology is utilized to carry out government activities more effectively. One form of implementing e-government is through the application of e-inventory. The purpose of developing this application is to provide a solution to issues related to documenting state-owned goods, such as errors in manual data recording, lack of real-time data updates for the goods, and difficulties in accessing data during inspections conducted by the Inspectorate or the Financial Audit Agency (BPK). These problems often occur in government offices with a large inventory, such as the Regional People's Representative Council of Berau (DPRD KAB.Berau), which still faces challenges in recording inventory items. Therefore, an Android-based e-inventory application has been developed to facilitate activities such as updating inventory data, documenting goods, and simplifying data retrieval.